PERAN PEMERINTAH DESA DALAM MENDUKUNG PELAYANAN KESEHATAN MASYARAKAT DESA LAYA KECAMATAN BATURAJA BARAT KABUPATEN OGAN KOMERING ULU - Revi Damayanti; Aprilia Lestari; Herni Ramayanti (Jurnal Ilmu Pemerintahan, 2025)
Community health services in Laya Village, West Baturaja District, Ogan Komering Ulu Regency still require support from the village government to operate optimally. This condition is influenced by low community participation, limited health socialization outside posyandu activities, and limited availability of medicines outside the posyandu schedule. The research problem of this study is how the role of the village government supports community health services in Laya Village, West Baturaja District, Ogan Komering Ulu Regency. This study aims to identify the role of the village government in supporting community health services in Laya Village. The study using a descriptive qualitative approach. Data were collected through interviews, observation, and documentation. This study employs the theory of government roles proposed by Ryaas Rasyid with three indicators, namely facilitator, dynamizer, and regulator. The results show that the role of the village government as a facilitator is realized through the provision of posyandu facilities and infrastructure and the allocation of health budgets in the Village Revenue and Expenditure Budget. The role as a dynamizer is carried out by encouraging community participation in posyandu activities through cadres by delivering information on activity schedules and providing health education during activities, yet these efforts have not been implemented intensively outside posyandu activities, resulting in uneven participation.The conclusion shows that the village government role exists but remains suboptimal. It recommends stronger health socialization, improved cadre training, and structured supervision and evaluation for community health services improvement in Laya Village.